The Geostrategic Significance of China's Engagement in Pakistan: A Regional Outlook (Journal of Social Sciences Review, 2023)
China's strategic engagement with Pakistan has become a focal point in global geopolitics, reflecting a profound shift in regional power dynamics. This article examines the geostrategic significance of China's involvement in Pakistan within a regional context, aiming to unravel the multifaceted dimensions of this strategic partnership and its implications for South Asia's geopolitical landscape. The historical backdrop of China-Pakistan relations, dating back to the 1950s, sets the stage for a robust partnership characterized by economic cooperation, military collaboration, and shared geopolitical objectives. Economic cooperation, exemplified by the China-Pakistan Economic Corridor (CPEC), aims to reshape Pakistan's economic landscape through infrastructure development and industrial collaboration. Moreover, military and defense cooperation underscores the shared security concerns between China and Pakistan, with joint exercises and arms sales reflecting their strategic alignment. This partnership has implications for regional security dynamics, particularly in relation to India and Afghanistan, shaping the broader geostrategic landscape of South Asia. Beyond bilateral relations, China's engagement in Pakistan influences regional responses and reactions, with neighboring countries like India, Afghanistan, and Iran navigating the evolving geopolitical dynamics. The study contributes valuable insights into the interplay between global powers and regional actors, shedding light on the evolving strategic landscape of South Asia and its implications for regional stability and security.
Keywords: China-Pakistan Relations; Geostrategic Significance; Military Collaboration; Economic Cooperation; Regional Outlook